THE USE OF ENREKANG FOLKTALES TO IMPROVE THE STUDENTS - St. Nuraysia Daud; Nurdevi Bte Abdul; Wildhan Burhanuddin (FKIP Unismuh Makassar, 2021)
This research aimed to find out whether or not the use of Enrekang`s folktales can improve the students` speaking skill in learning Englis that the eleventh grade students of Man Enrekang, Enrekang and whether or not the use of Enrekang`s folktales can improve the students` speaking skill in learning Englishat the eleventh grade students of Man Enrekang, Enrekang. The result of analysis showed (1) the use of Enrekang`s folktales make the students more confidence, relax and very helpful in learning English. It also can be seen in mean score (X1) of the pre test was 5.55 and in post test (X2) was 8.3. . Then, the result of t-test = 17.18. So, where it is greater than t-table (1.729) and it means that there was a significance increase after used Enrekang`s folktales as a media.H0 was rejected and H1 is accepted. Therefore, the used of Enrekang`s folktales in learning English at the Eleventh grade students of Man Enrekang, could improve the students` speaking skill.